Increased Immunosignals of Collagen IV and Fibronectin Indicate Ischemic Consequences for the Neurovascular Matrix Adhesion Zone in Various Animal Models and Human Stroke Tissue - Michalski, Dominik; Spielvogel, Emma; Puchta, Joana; Reimann, Willi; Barthel, Henryk; Nitzsche, Björn; Mages, Bianca; Jäger, Carsten; Martens, Henrik; Horn, Anja K. E.; Schob, Stefan; Härtig, Wolfgang (Frontiers in Physiology, 2020)
Ischemic stroke causes cellular alterations, depicted by the neurovascular unit (NVU) comprising neurons, glia and the vasculature, and also affects the blood-brain barrier (BBB) and adjacent extracellular matrix (ECM). Notably, limited data is available for the zone between the NVU and ECM that has not yet considered for neuroprotective approaches. This study describes ischemia-induced alterations for two main components of the neurovascular matrix adhesion zone (NMZ), i.e. collagen IV as basement membrane constituent and fibronectin as crucial part of the ECM, in conjunction with traditional NVU elements. For spatio-temporal characterization of these structures, multiple immunofluorescence labeling was applied to tissues affected by focal cerebral ischemia using a filament-based model in mice (4, 24 and 72 hours of ischemia), a thromboembolic model in rats (24 hours of ischemia), a coagulation-based model in sheep (two weeks of ischemia), and human autoptic stroke tissue (three weeks of ischemia). An increased fibronectin immunofluorescence signal demarcated ischemia-affected areas in mice, along with an increased collagen IV signal and BBB impairment indicated by serum albumin extravasation. Quantifications revealed a region-specific pattern with highest collagen IV and fibronectin intensities in most severely affected neocortical areas, followed by a gradual decline towards the border zone and non-affected regions. Comparing 4 and 24 hours of ischemia, the subcortical fibronectin signal increased significantly over time, whereas neocortical areas displayed only a gradual increase. Qualitative analyses confirmed increased fibronectin and collagen IV signals in ischemic areas from all tissues and time points investigated. While the increased collagen IV signal was restricted to vessels, fibronectin appeared diffusely throughout the parenchyma with focal accumulations associated with the vasculature. Integrin α5 appeared enriched in the vicinity of fibronectin and vascular elements, while most of the non-vascular NVU elements showed complementary staining patterns referring to fibronectin. This spatio-temporal characterization of ischemia-related alterations of collagen IV and fibronectin in various stroke models and human autoptic tissue shows that ischemic consequences are not limited to traditional NVU components and the ECM, but also involve the NMZ. Future research should explore more components and the pathophysiological properties of the NMZ as a possible target for novel neuroprotective approaches.